1993
DOI: 10.1136/bmj.306.6872.249
|View full text |Cite
|
Sign up to set email alerts
|

Death from cancer at home: the carers' perspective.

Abstract: Objectives-To collect information from principal carers ofpeople who had died at home with cancer; to identify areas ofsupport which need improvement.Design-Semistructured interviews with carers two to four months after the death.Setting

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
67
0
6

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(79 citation statements)
references
References 4 publications
6
67
0
6
Order By: Relevance
“…Kanser hastalarının orta veya kuvvetli düzeyde ağrı deneyimledikleri bulunmuştur. [8][9] Akut ağrı ani doku hasarının açığa çıkardığı prostoglandin, serotonin, histamin, bradikinin ve P maddesi nedeniyle olurken [10] ; kronik ağrı KT bağlı periferal nöropati; RT bağlı brakial plexopati, RT ve cerrahi tedaviye bağlı pelvik ağrı nedeniyle oluşabilir. [11] Kronik ağrı varlığı, ayaktan takip edilen kanser hastalarının ortalama %50'sinde, metastatik kanser hastalarının ise %80-90'ında görülmektedir.…”
Section: Ağrıunclassified
See 1 more Smart Citation
“…Kanser hastalarının orta veya kuvvetli düzeyde ağrı deneyimledikleri bulunmuştur. [8][9] Akut ağrı ani doku hasarının açığa çıkardığı prostoglandin, serotonin, histamin, bradikinin ve P maddesi nedeniyle olurken [10] ; kronik ağrı KT bağlı periferal nöropati; RT bağlı brakial plexopati, RT ve cerrahi tedaviye bağlı pelvik ağrı nedeniyle oluşabilir. [11] Kronik ağrı varlığı, ayaktan takip edilen kanser hastalarının ortalama %50'sinde, metastatik kanser hastalarının ise %80-90'ında görülmektedir.…”
Section: Ağrıunclassified
“…[8][9][10][11] Bu nedenden dolayı sağlık personeli; [11] • Hasta ve ailesi ile güven ilişkisi kurmalı,…”
Section: Ağrıunclassified
“…5 However, studies indicate that GP involvement is associated with facilitating home death. [6][7][8][9] Furthermore, despite earlier studies identifying considerable dissatisfaction with symptom control in a primary care setting, 3,10 satisfaction with GPs was still rated high 3 and relatives valued the involvement of GPs. 11,12 All in all, it suggests that good palliative care amounts to more than simply a certain degree of symptom control.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence of room for improvement in the quality of care that patients and their families receive (2,(4)(5)(6)(7). For example, GPs in West Cumbria, England, reported that 14% of patients had uncontrolled pain (2), and 19% of GPs questioned in another survey considered that at least 20% of patients have unsatisfactorily controlled pain ( 13).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge for educators is therefore "to stimulate and motivate colleagues to practise patient centred medicine in this difficult and demanding field" (7). Audit is a valuable method of education (8).…”
mentioning
confidence: 99%